Two Types of Prothrombin in Vitamin K Deficiency - Hemker, H. C; Muller, Annemarie D.; Loeliger, E. A (Thrombosis and Haemostasis, 1970)
In vitamin K deficiency (either absolute or induced by oral anticoagulants) two types of prothrombin occur. One is not distinguishable from normal prothrombin. It generates thrombin quickly in a medium in which the factors V, VII and X, thromboplastin and Ca++ are present in sufficient amounts. The other is converted into thrombin much more slowly under the same conditions. In the onestage prothrombin assay only the first form is measured, in a two-stage prothrombin assay both forms are estimated. This accounts for the well-known discrepancy between these two tests in vitamin K deficiency. The abnormal prothrombin can be considered one of the Proteins Induced by Vitamin K Absence. The occurrence of this kind of proteins fits in the concept of the action of vitamin K as a co-factor in a system that converts polypeptide-precursors into coagulation factors.